Carotid‐Femoral Pulse Wave Velocity as a Risk Marker for Development of Complications in Type 1 Diabetes Mellitus - Ninna Hahn Tougaard; Simone Theilade; Signe Abitz Winther; Nete Tofte; Tarunveer Singh Ahluwalia; Tine Willum Hansen; Peter Rossing; Marie Frimodt-Møller (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background The value of carotid‐femoral pulse wave velocity (cfPWV) as risk factor for development of complications in type 1 diabetes mellitus remains to be determined. We investigated associations between cfPWV and renal outcomes, cardiovascular events, and all‐cause mortality in people with type 1 diabetes mellitus. Methods and Results cfPWV was measured with SphygmoCor in 633 people with type 1 diabetes mellitus. Median (interquartile range) follow‐up was 6.2 (5.8−6.7) years. End points included progression in albuminuria group, decline in estimated glomerular filtration rate (eGFR) ≥30%, end‐stage kidney disease, cardiovascular event, mortality, and a composite renal end point. Hazard ratios (HRs) were calculated per 1‐SD increase in cfPWV. Adjustments included age, sex, hemoglobin A1c, mean arterial pressure, body mass index, low‐density lipoprotein cholesterol, smoking, urine albumin excretion rate, and eGFR. The cohort included 45% women, mean (SD) age was 54 (13) years, mean (SD) eGFR was 83.2 (27.9) mL/min per 1.73 m2, and mean (SD) cfPWV was 10.4 (3.3) m/s. Median (interquartile range) albumin excretion rate was 17 (17‐63) mg/24 h. After adjustment, higher cfPWV was associated with increased hazard of progression in albuminuria (HR, 1.59; 95% CI, 1.10−2.32); decline in eGFR ≥30% (HR, 1.38; 95% CI, 1.06−1.79); cardiovascular event (HR, 1.31; 95% CI, 1.01−1.70); mortality (HR, 1.36; 95% CI, 1.00−1.85); and the composite renal end point (HR, 1.30; 95% CI, 1.04−1.63), but not with end‐stage kidney disease (HR, 1.18; 95% CI, 0.62−2.26). Higher cfPWV was associated with steeper yearly increase in albumin excretion and steeper yearly decline in eGFR after adjustment (P=0.002 and P=0.01, respectively). Conclusions cfPWV was associated with increased hazard of renal outcomes, cardiovascular event, and mortality. cfPWV may be suited for risk stratification in type 1 diabetes mellitus.